Recurrent SMARCB1 Inactivation in Epithelioid Malignant Peripheral Nerve Sheath Tumors. (June 2019) - Schaefer, Inga-Marie; Dong, Fei; Garcia, Elizabeth P.; Fletcher, Christopher D.M.; Jo, Vickie Y.
Abstract : Epithelioid malignant peripheral nerve sheath tumors (EMPNST) are characterized by diffuse S-100 and SOX10 positivity, frequent immunohistochemical loss of SMARCB1 expression (70%), and rare association with neurofibromatosis type 1. Some cases arise in a preexisting epithelioid schwannoma (ESCW), which also show SMARCB1 loss in 40% of cases. To date, little is known about the genomic landscape of this distinctive variant of malignant peripheral nerve sheath tumor. The aim of this study was to use targeted next-generation sequencing to identify recurrent genomic aberrations in EMPNST and a subset of ESCW, including the basis of SMARCB1 loss. Sixteen EMPNSTs (13 SMARCB1-lost, 3 SMARCB1-retained) and 5 ESCWs with SMARCB1 loss were selected for the cohort. Sequencing identified SMARCB1 gene inactivation in 12/16 (75%) EMPNST and all 5 (100%) ESCW through homozygous deletion (N=8), nonsense (N=7), frameshift (N=2), or splice site (N=2) mutations; 2 EMPNSTs harbored 2 concurrent mutations each. SMARCB1 immunohistochemistry status and SMARCB1 alterations were concordant in 20/21 of the sequenced tumors. Additional genetic alterations in a subset of EMPNST included inactivation of CDKN2A and gain of chromosome 2q. Among SMARCB1- wild-type EMPNSTs there were single cases each with NF1 and NF2 mutations. No cases had SUZ12 or EED mutations. In summary, we identified recurrent SMARCB1 alterations in EMPNST (and all 5 SMARCB1-negative ESCWs tested), supporting loss of SMARCB1 tumor suppressor function as a key oncogenic event. SMARCB1-retained EMPNSTs lack SMARCB1 mutations and harbor different driver events.